Identification of and Support for Children of Mentally Ill Parents: A 5 Year Follow-Up Study of Adult Mental Health Services - Lauritzen, Camilla; Reedtz, Charlotte; Rognmo, Kamilla; Nilsen, Miriam A.; Walstad, Anja (Frontiers in Psychiatry, 2018)
Background: Children of parents with mental disorders are more likely to develop mental difficulties during their childhood and adulthood. Based on this knowledge, the Norwegian health legislation has been amended to better identify and protect children of parents with a mental illness. In this project, two interventions were implemented in a regional clinic for adult mental health services, both aimed to support healthcare professionals in identifying and providing support for children of patients within adult mental health services. The process of changing relevant practice to become more family-focused was evaluated in 2010 and 2013, and the results showed some changes slowly materializing in the adult mental health services. The purpose of the current study was to investigate long-term effects of the interventions at five year follow-up (2015). The main aim was to investigate whether the workforce perceived that their clinical practice had changed as a result of the legislative change and the implemented interventions. Method: This longitudinal study consists of a pre-test, post-test and follow-up test. The sample (N = 219 at pre-test, N = 185 by post-test and N = 108 on follow-up test) included healthcare staff from a participating hospital, responding to an online survey about their routines for identifying children of patients, their attitudes, as well as concerns and expectations related to having a child perspective in their clinical work. Employee experiences with family conversations were also investigated, as well as their knowledge about the consequences parents' mental disorders may have for children. Results: Our findings showed a significant increase in participants identifying children of patients between pre- and post-measurement but a minor, non-significant increase at follow-up measurement. There was no significant increase of participants who reported that they had a lot of experience with family conversations. From post-test to follow-up, there was no increase in the workforce’ reported positive attitudes, knowledge or expectations about the effects of the interventions. Conclusion: There have been some changes in clinical practice, but it seems that the changes required by law are a very time consuming process. It is necessary to increase the pace of the implementation process.